Nematogalectin, a nematocyst protein with GlyXY and galectin domains, demonstrates nematocyte-specific alternative splicing in Hydra - Hwang, Jung Shan; Adamczyk, Patrizia; Özbek, Suat; Holstein, Thomas W. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
National Academy of Sciences
Gesehen am 16.02.2017